Synthesis of novel low-molecularweight polytetrafluoroethylene and tetrafluoroethylene copolymers for pyrotechnic applications - Crouse, Philippus L. (University of Pretoria, 2021)
Thesis (PhD (Chemical Engineering))--University of Pretoria, 2017.